PENGARUH KEPUTUSAN UTAMA TERHADAP NILAI PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2016 - Tannia Tannia; Claryn Tanado; Elisa Putri (Universitas Bunda Mulia, 2018)
The purpose of this research is to determine effect of the main decisions on firm value ofmanufacturing companies listed in Indonesia Stock Exchange period, of 2012-2016. The main decisionsare three main functions of a financial manager in every firm. This research is a quantitative researchthat uses panel data and processing the panel data with E-Views. Sample of this research are 120manufacturing companies listed in Indonesia Stock Exchange.The results that there are a significanteffect of Dividend Decision on firm value and there is an insignificant effect of investment and fundingdecision of manufacturing companies listed in Indonesia Stock Exchange, period of 2012-2016.Key words: Investment, Funding, Dividend, Value of Firm